Incidence of Hip Dysplasia Associated With Bladder Exstrophy. Issue 8 (December 2016) - Mundy, Andrew; Kushare, Indranil; Jayanthi, Venkata R.; Samora, Walter P.; Klingele, Kevin E.
Abstract : Background: Exstrophy of the bladder is a rare congenital defect seen in 2.15 children out of every 100, 000 live births, with the most severe variant, cloacal exstrophy (CE), only occurring in 1 in 200, 000. Developmental dysplasia of the hip (DDH) describes a spectrum of disease ranging from mild hip instability to frank dislocation. Underlying malformations, such as myelomeningocele and arthrogryposis, are often associated with the most severe variant of hip dysplasia, teratologic hip dislocation. The varying degrees of severity in DDH have been encountered in classic bladder exstrophy (CBE) patients, but the exact incidence is unknown. We sought to determine the incidence of DDH in CBE and CE patients. Methods: We performed a retrospective review of all children with CBE or CE presenting to a single pediatric center between 1994 and 2014. Each chart was reviewed for correct diagnosis of CBE or CE, patient age and demographics, associated medical conditions, pertinent surgeries performed, and the age at operation. Patient imaging was reviewed to determine whether bilateral hip imaging was available. Results: In a 20-year retrospective review, we identified 66 patients who were diagnosed with either CBE or CE and had available hip imaging (38 males and 28 females). Of these, 11 patients were found to have radiographic evidence of DDH, for an incidence of 16.7% (11/66). Five of these patients had CE, whereas 6 presented with CBE. The first radiographic evidence of DDH was noted at a mean age of 5.75 years (range, birth to 22 y). Conclusions: We advocate the use of routine hip screening ultrasound in all infants born with either CBE or CE. Early identification of DDH in these patients may allow additional treatment options to coincide with frequently used osteotomy and orthopaedic interventions. Level of Evidence: Level III—retrospective study.